Analysis of Potential Sectors in Determining Development Priorities in Bintuni Bay Regency - Hasyim, Abddurrahmat (Journal of International Conference Proceedings, 2023)
Economic development is a process to improve the standard of living and welfare of society. The goal of economic development is to realize better economic growth and absorb a larger workforce. Regional development carried out in an integrated manner through the preparation of spatial plans must be directed at solving the main problems in the region, in terms of welfare and economic growth. This study aims to determine the potential economic sectors to be developed in Teluk Bintuni Regency. This research uses the LQ analysis method, Growth Ratio Model analysis, and Klassen Typology.Â  The data used is secondary data in the form of GRDP of Teluk Bintuni Regency and West Papua Province in 2012-2022 sourced from the Central Statistics Agency (BPS). The analysis was carried out by determining the base sector, then formulating a sector typology using the Klassen Typology, and finally describing potential economic activities or sectors based on the criteria for regional economic structure growth using the Growth Ratio Model.